Factors affecting compliance on generics prescribing a government hospital experience. - Bolo, Renato B.
This study describes the status of compliance of physicians and dentists on generics prescription at DFBDSMH; and to determine the variables that influence the compliance of DFBDSMH physicians and dentist in generics prescribing. It is a combined qualitative and quantitative descriptive cross-sectional study on the possible reasons affecting compliance of physicians and dentists with the generics prescribing at DFBDSMH. Respondents were selected by total enumeration of all physicians and dentists practicing at DFBDSMH. Prescriptions were collected from the hospital pharmacy via systematic sampling of the prescriptions made for the last six months. Interview with the respondents were done via self-administered questionnaire. Focus group discussion with selected respondents was conducted to expound on the reasons they have provided. Key informant interview with the Chief Hospital Pharmacist and the DOH-FDA representative were done to explicate issues given by the respondents related to compliance. Twelve out of 29 of the respondents (41.38%) fully complied with the generics-only prescription. The remaining 17 respondents (58.62%) were determined to have contained brand names in some of their prescriptions. Out of 1,799 prescriptions examined, 1,590 (88.38%) were compliant and only 209 (11.62%) were non-compliant to generics prescribing. Statistically significant results were seen on two variables affecting the prescribing habits of respondents, namely 1) the confidence of the respondents on the efficacy of the drug influences their prescribing habits, and 2) the gifts / incentives which the respondents get when they direct their patients to particular pharmacy outlets. Recommendations include: 1) coordinated efforts with Food and Drug Administration and DFBDSMH on re-orientation and reinforcement of the Generics Law and the Cheaper Medicines Law, specifically on the importance and impact of generics prescribing; and reassurance of the quality of the generic drugs; 2) DFBDSMH's Therapeutics Committee should review the existing policies and make necessary revisions; it should strictly monitor and enforce the Generics Law and Cheaper Medicines Law; and 3) The Chief Pharmacist should make monthly reports on the compliance of generic prescriptions of the physicians and dentists and those who are violating the generics provision of the law.